Mixing It Up : A South-Watcher's Miscellany - Reed, John Shelton (Book collections on Project MUSE., 2018)
"Too often depicted as a region with a single, dominant history and a static culture, the American South actually comprises a wide range of unique places and cultures, each with its own history and evolving identity. John Shelton Reed's Mixing It Up is a medley of writings that examine how ideas of the South, and what it means to be southern, have changed over the last century. Through essays, op-eds, speeches, statistical reports, elegies, panegyrics, feuilletons, rants, and more, Reed's penetrating observations, wry humor, and expansive knowledge help him to examine the South's past, survey its present, and venture a few modest predictions about its future. Touching on an array of topics from the region's speech, manners, and food, to politics, religion, and race relations, Reed also assesses the work of other pundits, scholars, and South-watchers."--Publisher's web-site.